Incidencia de la tasa de interés en la rentabilidad de empresas microfinancieras en el Perú: 2013-2018 - Pinedo Rubio, Evelyn Yahaira (2020)
Determine the incidence of the interest rate on the profitability of microfinance companies in Peru: 2013-2018. This study is a type of non-experimental investigation of longitudinal and correlational cutting. It was found that the average interest rate (B1 = -1.29) and late payment (B2 = -1.03) have a significant and inverse incidence; while solvency (B3 = 0.54) and liquidity (B4 = 0.06) have a direct and significant impact. With a (R2 = 0.956) in the profitability of microfinance companies in Peru, 2013-2018. The average interest rate charged by microfinance companies to microenterprises is: Below 40% (Mitsui, Trust, Procurement and TFC). over 60% (Create and Effective). And Crediscotia and Universal have average rates between 40% and 50%. On average, microfinance companies maintain their solvency ratio between 15 to 18 percentage points. With respect to the efficiency ratio, this has experienced a permanent increase, based on the acquisition and implementation of new technologies for the different microfinance institutions.